Unusual rearrangement of imidazo[1, 5-a]imidazoles and imidazo[1, 2-b]pyrazoles into imidazo[1, 5-a]pyrimidines and pyrazolo[1, 5-a]pyrimidines. Issue 50 (16th September 2019) - Gambouz, Khadija; Driowya, Mohsine; Loubidi, Mohammed; Tber, Zahira; Allouchi, Hassan; El Kazzouli, Saïd; Akssira, Mohamed; Guillaumet, Gérald
Abstract : A multicomponent reaction giving easy and cheap access to a variety of bicyclic 5, 5-fused hetero-rings has been developed. Abstract : A multicomponent reaction giving easy and cheap access to a variety of bicyclic 5, 5-fused hetero-rings has been developed. Then, an usual rearrangement of imidazo[1, 5- a ]imidazoles or imidazo[1, 2- b ]pyrazoles leading to bi-heterocyclic imidazo- and pyrazolo[1, 5- a ]pyrimidines in the presence of a specific amount of I2 in THF at room temperature has been achieved. This new method enables the hitherto unreported synthesis of functionalized imidazo- and pyrazolo[1, 5- a ]pyrimidines.